(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: Dengue is a global challenge in public health, particularly in Brazil, where its incidence is increasing. Present in more than 100 countries, the disease ranges from asymptomatic forms to severe cases, which can be fatal. Among the complications of dengue, rhabdomyolysis stands out, causing muscular deterioration and renal failure. Its occurrence in non-hemorrhagic cases is low, making early detection challenging. Objective: Raise awareness about the possibility of rhabdomyolysis associated with dengue in pediatric patients, aiming for early diagnosis and treatment to reduce the mortality rate. Case report: Male teenager, 13 years old, presenting with headache, fever, lethargy, retro-orbital pain, and positive serology for dengue (IgM). The patient developed the classic triad of rhabdomyolysis: muscle pain, weakness, and dark urine, associated with high levels of creatine kinase (41,993 U/L), a marker of muscle injury. There was an increase in liver transaminases, with values of 1958 U/L for aspartate aminotransferase and 978 U/L for alanine aminotransferase, indicating significant liver damage. Adequate fluid administration, a cornerstone in dengue treatment, contributed to the patient’s recovery. The patient progressed positively, was discharged after six days of hospitalization, without renal failure, experiencing complete recovery without additional complications. Conclusion: Recognizing rhabdomyolysis as a potential complication of dengue, especially in young individuals, is crucial for early diagnosis and treatment, reducing morbidity and mortality.